Potential use of zeolite on growth and developmnent of Kai Lan (Brassica oleraceae cv. Alboglabra - Muhammad Zulkhairi Abu Karim,
Vegetables are very important to our life. If there is no any leafy in our food, our meal will not be nutritionally complete. Leafy vegetables have several nutritional contents such as energy, moisture, protein, fat, fibre, ash and carbohydrate (Odhav et al., 2007). Most of leafy vegetables also have calcium, phosphorus, copper, sodium, manganese, zinc, magnesium and iron (Odhav et al., 2007). For Kai Lan, there have nutritional contents such as violaxanthin, neoxanthin, lutein/zeaxanthin, 1s.-Carotene, ascorbic acid, calcium, iron, zinc, carotenoids and glucosinolates (Hanson et al., 2011). In Malaysia, the area cultivated with vegetables are 35, 956 hectares and three percent of it which 1, 179 hectares are planted with Brassica oleraceae cv. Alboglabra or Kai lan (MOA, 2010). Valente et al. (1982), Burriesci et al. (1984), Gruener et al. (2003 and 2007), Gul et al. (2005), Mahmoodabadi et al. (2009), Ryakhovskaya and Gainatulina (2009) were conducted experiment with zeolite and peach, grapes, wheat, lettuce, radish, tomato, spinach, oat, potato and soybean. All these studies showed significant contributions of zeolite to all model crops. Valente et al. (1982) also have reported that tomato yield was increase with the application of zeolites. Meanwhile Burriesci et al. (1984) have produce two paper in the same year. For January, they reported utilization of zeolites in spinach growing and on October they reported effect of zeolites to peach and grapes growth. Gruener et al. (2003) were conducted common ion effects in zeoponic substrate regards to the growth of wheat. Zeoponic is terminology introduced by National Aeronautics and Space Administration (NASA). Gui et al (2005) have made comparison of the use of zeolite and perlite for crisp-head lettuce. Gruener et al (2007), have experimented plant productivity and characterization of zeoponic substrates after three successive crops of radish (Raphanus sativus). The latest zeolite and crop growth research were on 2009 by Ryakhovskaya and Mahmoodabadi et al. where both of them conducted zeolite application with potato, oat and soybean. From all researches, most of them said there were through zeolite application the yield of their crops were increased, shoot and root dry weight increased, zeolite have assisted in zeoponic systems to cultivated radish in Mars and Moon, zeolite resulted higher head mass for lettuce compared to perlite, effect to increased on fruit sizes and increased germinability of seeds. However, in Malaysia studies on zeolite are still scared, thus, this study was carried out with the following objectives : 1. To determine whether zeolites application can enhance growth of Brassica oleraceae var. Alboglabra. 2. To obtain optimum proportion of zeolite in the soilless media.